The evaluation of melatonin as a possible antidepressive - Skene, Debra Jean (Rhodes University, Faculty of Pharmacy, Pharmacy, 1980)
Melatonin, a hormone of the pineal gland, was evaluated in a variety of animal models of depression. Measurements of the frog righting reflex and rat locomotor activity showed that low doses of melatonin have a serotonin-like potentiating effect following monoamine oxidase inhibition. High doses of melatonin caused a reduction in the duration of rat immobility in the Porsolt model of depression and exerted a chlorpromazine-like effect on conditioned avoidance behaviour. In view of the indoleamine hypothesis of depressive disorders, the possibility of melatonin being a potential antidepressive is discussed and it is concluded that melatonin might be useful in the treatment of "agitated" depressions
Keywords: Melatonin; Antidepressants